Variasi Intraspesies Lactobacillus plantarum (Orla-Jensen) Bergey et al. Asal Sayur Asin Berdasarkan Analisis Molekuler - ., Sulistiani; ., Abinawanto; Sukara, Endang; Dinoto, Achmad; Mangunwardoyo, Wibowo (JURNAL BIOLOGI INDONESIA, 2015)
The current study is the first report on intraspecies analysis of L. plantarum from sayur asin in Indonesia using molecular approach. Three molecular techniques, i.e., restriction fragment length polymorphism (RFLP) 16S-23S rDNA intergenic spacer region (ISR), random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) and enterobacterial repetitive intergenic consensus (ERIC-PCR) were used to determine the intraspecies diversity of L. plantarum responsible for spontaneous fermentation in sayur asin. These methods were aimed to discriminate 46 isolates of L. plantarum isolated from sayur asin, including the type strain. PCR amplification of the 16S-23S rDNA ISR revealed two-bands profile of 800 and 600 bp specific to lactobacilli. RAPD-PCR and ERIC-PCR were very valuable in discriminating genetic polymorphism among L. plantarum isolates by producing bands ranged from 4-10 bands (360-2620 bp) and 6-12 bands (160-2900 bp), respectively. Dendograms generated from UPGMA cluster analysis based on RAPD-PCR and ERIC-PCR data showed that all isolates were grouped into three major clusters with 74% and 68.6% genetic similarity thresholds, respectively.The study indicated that strains belong to L. plantarum isolated from sayur asin were divided into three genotypic groups.ÃÂ Keywords: ERIC-PCR, Intraspecies, Lactobacillus plantarum, RAPD-PCR, RFLP 16S-23S rDNA ISRÃÂ